Fulfill Your Digital Preservation Goals with a Budget Studio - Zhou, Yongli (Information Technology and Libraries, 2016)
In order to fulfill digital preservation goals, many institutions use high-end scanners for in-house scanning of historical print and oversize materials. However, high-end scanners’ prices do not fit in many small institutions’ budget. As digital single-lens reflex (DSLR) camera technologies advance and camera prices drop quickly, a budget photography studio can help to achieve institutions’ preservation goals. This paper compares images delivered by a high-end overhead scanner and a consumer level DSLR camera, discusses pros and cons of using each method, demonstrates how to set up a cost efficient shooting studio, and presents a budget estimate for a studio.